Forkhead‐box R2 promotes metastasis and growth by stimulating angiogenesis and activating hedgehog signaling pathway in ovarian cancer. Issue 9 (26th June 2018) - Li, Bing; Huang, Wei; Cao, Ning; Lou, Ge
Abstract: Overexpression of forkhead‐box R2 (FoxR2) is related to metastasis and progression of tumor. However, its biological functions in ovarian cancer (OC) progression remain unclear. Herein, we aimed to explore the changes in biological functions and molecular events related to FoxR2 overexpression. We found that FoxR2 is upregulated frequently in OC where these events are associated with worse histologic grade and poor survival. Enhanced expression of FoxR2 was related to cell growth, migration, and epithelial‐mesenchymal transition, whereas silencing of FoxR2 suppressed these malignant phenotypes. In addition, angiogenesis was stimulated by FoxR2 overexpression by enhancing vascular endothelial growth factor expression. Further mechanistic investigations revealed that the increase in cell surface FoxR2 promoted sonic hedgehog binding and signaling. Inhibiting hedgehog pathway with sonidegib decreased FoxR2‐induced migration and lung metastasis of OC cells, establishing the critical role of hedgehog signaling in mediating the effects of FoxR2 expression. Taken together, our results indicate that FoxR2 overexpression in OC contributes to malignant behavior in cancer cells, at least in part through stimulating angiogenesis and activation of the hedgehog signaling pathway. Hedgehog signaling pathway activation may be the key in tumor progression mediated by FoxR2. Abstract : Our findings provide new information about the function of FoxR2 in ovarian cancer (OC); it also provides clues for developing new therapeutic drugs for OC.